Silencing of bach1 gene by small interfering RNA–mediation regulates invasive and expression level of miR-203, miR-145, matrix metalloproteinase-9, and CXCR4 receptor in MDA-MB-468 breast cancer cells - Reza Mohammadzadeh; Mojgan Saeid Harouyan; Seyed Mansour Ale Taha (Tumor Biology)
Background: Recently experimental validation of the networks revealed bach1, a basic leucine zipper transcription factor, as the common regulator of several functional invasive genes. The expression of bach1 and its target genes was linked to the higher risk of breast cancer recurrence in patients. The aim of this study was to investigate the effect of specific bach1 small interfering RNAs, on the invasive and expression level of miR-203, miR-145, matrix metalloproteinase-9, and CXCR4 receptor which play a role in cancer metastasis, in MDA-MB-468 cell lines. Methods: Small interfering RNA transfection was performed with transfection regent. The survival effects of small interfering RNA were determined using trypan blue assay cells. The expression level of messenger RNA and matrix metalloproteinase-9 to assess cell invasion and the expression level of miR-203, miR-145, and CXCR4 receptor were measured by quantitative real-time polymerase chain reaction analysis on the MDA-MB-468 cell lines. Results: Transfection with small interfering RNA significantly suppressed the expression of bach1 gene in dose-dependent manner after 48 h ( p  < 0.0001). A significant reduction in cell invasion and CXCR4 receptor, matrix metalloproteinase-9 expression were observed ( p  < 0.0001). It was also a dramatic increase in the expression level of miR-203 and miR-145 ( p  < 0.0001). Conclusions: Our results suggest that the bach1-specific small interfering RNA effectively decrease CXCR4 receptor, matrix metalloproteinase-9 expression and breast adenocarcinoma cells invasive, also increased the expression of tumor-suppressive microRNA-203 and miR-145. Thus, these microRNAs may play a role in invasive/metastasis of carcinogenic breast cancer cells. Therefore, bach1 knockdown can be considered as a potent adjuvant in breast cancer therapy.